Dampak Pengumuman Kebijakan BI 7 Days Repo Rate Pada Saham Yang Terdaftar Dalam Jakarta Islamic Index - TISOF AMRI IZAR AMINULLOH, 041411431069 (Departemen Ekonomi Syariah, FEB, Universitas Airlangga, 2019)
This research aims to find out and explain Jakarta Islamic Index market reaction caused by BI 7 Days Repo Rate announcement by Bank Indonesia on April 15th , 2016. The approach used in this research is quantitative approach by using event study method which is the approach that is specialized to analyze a particular event that is believed to have an impact or reaction. Data used is secondary data including announcement data, stock price, trading volume during the period of observation and period of estimation. The object of the research is all the issuer that listed in Jakarta Islamic Index. Period of observation is 31 days started from 15 days before the event date to 15 days after the event date meanwhile the period of estimation is 55 days before period of observation. The focus of the research is to see the reaction shown by the change of Average Abnormal Return and Trading Volume Activity using one sample t-test and paired sample t-test. Data processing used a statistical tool of Stata version 14 by determining level of significance of 5%. The results of the research show that there is a significant average abnormal return around the date of announcement and there is a significant difference in trading volume activity before and after the right issue.